The book of Hosea - Dearman, J. Andrew (John Andrew), 1951- (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2010)
J. Andrew Dearman considers the prophetic figure's historical roots in the covenant traditions of ancient Israel, includes his own translation of the biblical text, and masterfully unpacks Hosea's poetic, metaphorical message of betrayal, judgment, and reconciliation. --from publisher description
Includes bibliographical references (p. 60-73) and indexes.
Keywords: Bible. -- Commentaries